2015
DOI: 10.1111/jne.12299
|View full text |Cite
|
Sign up to set email alerts
|

The −216‐ to −100‐bp Sequence in the 5′‐Flanking Region of the Oxytocin Gene Contains a Cell‐Type Specific Regulatory Element for its Selective Expression in Oxytocin Magnocellular Neurones

Abstract: The oxytocin (OXT) gene is abundantly and highly selectively expressed in magnocellular neurones (MCNs) of the hypothalamic-neurohypophysial system. Previous DNA sequence deletion studies in vivo have shown that the -216- to -100-bp sequence in the 5'-flanking region of the oxytocin gene was required for its cell-type specific expression in the rat supraoptic nucleus. In the present study, we test the coupled hypotheses that this -216- to -100-bp sequence is responsible for (i) the selective expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Expression of oxytocin occurs in separate neuronal populations due to regulation in part by cis -elements (Gainer 1998). In particular, it was recently found that the -216- to -100-bp sequence in the 5′ flanking region of the oxytocin gene is responsible for its selective expression in oxytocinergic magnocellular neurons, while it is not sufficient by itself to induce oxytocin expression in vasopressin-magnocellular neurons (Fields and Gainer 2015). …”
Section: Oxytocin Synthesis Processing Release and Degradationmentioning
confidence: 99%
“…Expression of oxytocin occurs in separate neuronal populations due to regulation in part by cis -elements (Gainer 1998). In particular, it was recently found that the -216- to -100-bp sequence in the 5′ flanking region of the oxytocin gene is responsible for its selective expression in oxytocinergic magnocellular neurons, while it is not sufficient by itself to induce oxytocin expression in vasopressin-magnocellular neurons (Fields and Gainer 2015). …”
Section: Oxytocin Synthesis Processing Release and Degradationmentioning
confidence: 99%
“…One nuclear nonsynonymous mutation from arginine to cysteine in VTN occurred at the 5′ flanking region, which contains the promotor to regulate transcription and gene expression. Even though this mutation did not occur in the transcriptional binding sites, mutation in the flanking region has a high possibility to result in a change in transcription, regulation, or its function (Hayashi et al 1991;D'Souza et al 2004;Fields and Gainer 2015); thus, it might affect phylogenetic history as shown in the combined data of four genes (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone and other receptors can bind to the composite hormone response element (CHRE) in the promoter region of Oxt to activate transcription [16,17]. Genetic deletion of this region abolishes transcription, indicating the CHRE is required for proper regulatory control of Oxt [18]. A CpG dinucleotide flanks the 5 0 end of the CHRE but its potential role in the epigenetic regulation of Oxt in the PVN has not been examined.…”
Section: Introductionmentioning
confidence: 99%